The Recontruction Of “Borobudur Chair” An Indonesian Cultural Heritage - Widayat, Rahmanu; B Studyanto, Anung; ., Sholahuddin (2016)

(untitled)
This Borobudur chair is a very interesting object because it shows that 1,200 years ago Javanese people (those who lived in Java Island, Indonesia) had a tradition of sitting on a chair. This fact shows dissimilarity from the common opinion stating that Javanese people first encountered with a chair during the colonial era. Javanese people already had “sitting on a chair” tradition that is similar to ancient Egyptians, Greeks, Romans, and Chinese people who had adopted this custom before the Javaneses. “Borobudur Chair” is a reconstruction of a chair visual from the reliefs of Borobudur temple. It is made by interpreting the shape of the chair in the reliefs which is then translated into a replica. There are two main data for this research. First is the reliefs in Borobudur temple, and the main concern is the visual of chair that is similar with the contemporary chair. These visuals can be found in the section Karmawibhangga, engraved in 160 panels. They are not a continuous story, but pieces of the visuals of karma. Karma can be defined as actions derived from a cause (both physical causes and ideas) and consequences. This reasearch starts from the reconstruction process until the replica production of Borobudur chair. I do hope that this study can be one of the ways to preserve Indonesian cultural heritage and can be used today and in the future. The reconstruction process can be a way to preserve Indonesian heritage, such as I have done with this research